Clinical laboratory detection of carbapenem-resistant and carbapenemase-producing Enterobacteriaceae. Issue 8 (2nd August 2016) - Miller, Shelley; Humphries, Romney M.
ABSTRACT: Introduction : Carbapenemases, enzymes that hydrolyze carbapenem-class antimicrobials, pose serious clinical and diagnostic challenges, including their recent rapid spread among members of the Enterobacteriaceae, a family with no inherent carbapenem resistance. Currently there is no one-size-fits-all method for detecting carbapenem-resistant Enterobacteriaceae (CRE) in the laboratory, nor how to differentiate carbapenemase-producers (CP) from isolates that are carbapenem-resistant via other or combined mechanisms. Areas covered : This article reviews definitions for CRE and CP-CRE, and discusses current phenotypic and molecular methods available to the clinical laboratory for the detection of both CP and non-CP CRE. Expert commentary : Routine evaluation of carbapenem resistance mechanism by the routine clinical laboratory are not necessary for patient care, as clinical breakpoints best predict response. However, evaluation for carbapenemase is integral to infection control efforts, and laboratories should have the capacity to do such testing, either in house or by submitting isolates to a reference laboratory.